Impact of Air-Purifying Plants on the Reduction of Volatile Organic Compounds in the Indoor Hot Desert Climate - Al Qassimi, Nahla; Jung, Chuloh (Frontiers in Built Environment, 2022)
Due to hot desert weather, residents of the United Arab Emirates (UAE) spend 90% of their time indoors, and the interior environment of the newly built apartments with inappropriate material and ventilation is causing sick building syndrome (SBS), faster than in any other country. NASA studies on indoor air pollutants indicate that the usage of 15–18 air-purifying plants in 18–24 cm diameter containers can clean the air in an average 167.2 m2 house (approximately one plant per 9.2 m2). This study investigates the effect of three different types of air-purifying plants, Pachira aquatica, Ficus benjamina, and Aglaonema commutatum, in reducing volatile organic compounds (VOCs) and formaldehyde (CH2O) in hot desert climate. An experiment is performed in which the CH2O and VOCs concentrations are measured in two laboratory spaces (Room 1 and Room 2). Different volumes (5 and 10% of the laboratory volume) of target plants are installed in Room 1, whereas Room 2 is measured under the same conditions without plants for comparison. The results show that the greater the planting volume (10%), the greater is the reduction effect of each VOCs. In summer in hot desert climate, the initial concentration (800 µg/cm3) of CH2O and VOCs is higher, and the reduction amount is higher (534.5 µg/cm3) as well. The reduction amount of CH2O and toluene (C7H8) is particularly high. In the case of C7H8, the reduction amount (45.9 µg/cm3) is higher in summer with Aglaonema commutatum and Ficus benjamina. It is statistically proven that Ficus benjamina is most effective in reducing CH2O and C7H8 in an indoor space in hot desert climate. The findings of this study can serve as basic data for further improving the indoor air quality using only air-purifying plants in hot desert climate of the United Arab Emirates.